2022
DOI: 10.1177/10547738221101729
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Active External Warming of Patient Concurrently With Ice Application on the Incision Site on Post-Thoracotomy Pain and Analgesic Consumption

Abstract: The aim of study is to investigate the effects of active external warming of patient concurrently with application of ice to incision site on thoracotomy pain and analgesic consumption. The research is a quasi-experimental design with control and study groups. The study was conducted in 2018 and 2019. A total of 70 patients were included in the study: 35 in the control group and 35 in the study group. The mean verbal pain scale values were significantly lower in the intervention group (2.85 point) than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…It has been widely practiced for post thoracotomy pain by rehabilitation and external warming methods. Kol et al ( 41 ) investigated that the effects of active external warming of patient concurrently with application of ice to incision site on thoracotomy pain and analgesic consumption and demonstrated that active external warming and ice application on the incision area, could reduce opioid consumption the intensity of thoracotomy pain. Transcutaneous electrical stimulation has been used as a form of physical therapy for postoperative pain after thoracic surgery ( 42 , 43 ).…”
Section: Othersmentioning
confidence: 99%
“…It has been widely practiced for post thoracotomy pain by rehabilitation and external warming methods. Kol et al ( 41 ) investigated that the effects of active external warming of patient concurrently with application of ice to incision site on thoracotomy pain and analgesic consumption and demonstrated that active external warming and ice application on the incision area, could reduce opioid consumption the intensity of thoracotomy pain. Transcutaneous electrical stimulation has been used as a form of physical therapy for postoperative pain after thoracic surgery ( 42 , 43 ).…”
Section: Othersmentioning
confidence: 99%